A capabilities approach to educating the deliberate professional: theory and practice - McLean, Monica; Walker, Melanie (Springer International Publishing, 2016)
This chapter casts ‘deliberate professionalism’ as ‘public-good professionalism’. It brings to thinking about educating the deliberate professional a ‘capabilities approach’ lens, as it has been developed by Amartya Sen and Martha Nussbaum. The authors draw on a study of five professional education departments in three South African universities that collaboratively generated a Public-Good Professional Capabilities Index to discuss pedagogical aims and practice. The paper shows how a capability framework played out in the pedagogical practices in different university departments. It is argued that the capabilities approach can offer a contextualised, rounded and feasible lens on educating the deliberate professional.